Water flow and salt transport in bare saline‐sodic soils subjected to evaporation and intermittent irrigation with saline/distilled water. (14th May 2019) - Liu, Dongdong; She, Dongli; Mu, Xingmin
Abstract: Sustainable development of coastal reclamation areas is severely restricted by the high soil salt content and irrigation water salinity. We investigated the water flow and salt transport in open soil columns subjected to evaporation and intermittent irrigation with saline/distilled water by long‐term wetting–drying cycles. The study included two different soil materials (silt loam and silty clay) with four to five soil sodicity levels. Three groups of experiments with three replicates were imposed: silt loam × 5 sodicity level, silty clay × 5 sodicity level, and 2 soil textures × 5 irrigation water qualities. Three irrigations were conducted in Spring to early Autumn (March 2, June 30, and September 8), whereas the soil columns were subjected to the natural evaporation without rainfall throughout the period September 9 to March 1. The average daily soil evaporation rate significantly decreased with the soil clay content ( pr  = −0.55; P  < 0.001), soil exchangeable sodium percentage ( pr  = −0.54; P  < 0.001), and irrigation water salinity ( pr  = −0.32; P  < 0.001). The soil properties were the major factors responsible for controlling evaporation, whereas the irrigation water salinity was the less important factor. Soil salt distribution was significantly affected by the soil clay content ( pr  = 0.82; P  < 0.001), soil depth ( pr  = 0.68; P  < 0.05), soil exchangeable sodium percentage ( pr  = 0.85; P  < 0.001), and irrigation water salinity ( pr  = 0.37; P  < 0.001). The magnitudes of the steady‐state infiltration rate i c and soil saturated hydraulic conductivity Ks were largely reduced by wetting–drying cycles, especially for the silty clay. Understanding water flow and salt transport in saline‐sodic soils subjected to evaporation and intermittent irrigation with saline/distilled water is important for improving the soil desalination project and strategy.